Discovering dimensional differences among Holstein and conventional beef middle meat cuts and consumer preferences for appearance - Steger, Jessica Renee, author; Woerner, Dale R., advisor; Belk, Keith E., committee member; Tatum, J. Daryl, committee member; Pendell, Dustin L., committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: Holstein; conformation; muscle; beef; beta-agonist